KONSEP URANG SABANA URANG DALAM PEPATAH ADAT MINANGKABAU - Rizal Mustansyir; Misnal Munir (Jurnal Filsafat "WISDOM", 2009)
AbstractAccording to Wilhelm Dilthey’s hermeneutic perspective,there are six points in reinterpreting the Minangkabau’s traditional aphorism “Urang sabana urang”. First, understanding of Minangkabau’s way of life is a general process, included in an ordinary life which is expressed in the aphorism. Second, theexpression of the aphorism is called “ausdruck”, Minangkabau’sexpression of life experiment and historicity. Third, humancharacteristics in Minangkabau’s aphorism consist of: “urang,urang-urang, tampan urang, angkuh-angkuh urang, urangurangan, urang sabana urang”. Fourth, “urang sabana urang” is a man who has excellent characteristics. Fifth, the globalization influence and the modern culture have changed Minangkabau’s insight of “urang sabana urang” concept so that it needs a reinterpretation in order to be understood by youth of Minang. Sixth, the epistemological dimension in Minangkabau’s aphorism synthesizes an empirical aspect and rationality. The metaphysical dimension of the aphorism shows a relation between tradition and religion so that it arise the principle of “adat basandi syarak, syarak basandi kitabullah”. The axiological dimension in the aphorism is seen as a criterion of values which is an obligation for Minangs to prevent their identity as” urang sabana urang”.Keyword: urang sabana urang, adat basandi syarak, syarakbasandi kitabullah, Minangkabau custom aphorism.